Barriers To E-Commerce Advertising Adoption: A Qualitative Study of Sellers on an Indonesian Marketplace - Ratri Ayu Salmadewi; Sahat Hutajulu (Green Publisher Indonesia, 2025)
Despite digital advertising becoming more important in providing business advantage, many sellers in Indonesia remain hesitant to adopt e-commerce advertising tools. This study investigates the main barriers that prevent sellers from using advertising features on a major Indonesian marketplace. A qualitative approach was applied through semi-structured interviews with ten sellers, including current users, former users, and non-users. This study offers a novel contribution by exploring seller resistance from an experience-based perspective, which has not been widely explored in existing adoption research. The study uses a framework analysis method to identify eight main barriers including performance expectancy, effort expectancy, social influence, facilitating conditions, price value, habit, personal innovativeness, and digital advertising literacy. While most sellers found the platform easy to use, concerns about performance outcomes, cost justification, and lack of advanced knowledge limited adoption. Social factors and marketing preferences also influenced seller decisions. To strengthen the findings, this study uses a triangulation method by comparing the qualitative results with a previous quantitative study. This approach provides a clearer view of seller adoption behavior by confirming key factors and highlighting both aligned and differing insights. These findings provide a clearer understanding of why some sellers resist using e-commerce advertising and emphasize the need to address barriers and concerns to encourage wider tools adoption.